Role of microstructural white matter changes of somatosensory cortex in stress among non-clinical population: A diffusion tensor imaging study - Wan Adibah Nadiah, Abd Razak; Rajeev Shamsuddin, Perisamy; Nor Saradatul Akmar, Zulkifli; Khairul Salleh, Abdul Basit; Muzaimi, Mustapha; Mohd Khairul Izamil, Zolkefley (Kulliyyah of Medicine, IIUM, 2024)
Introduction: Stress is a common response to stressors or potential threats, resulting in physical, affective, and cognitive changes. Emotions are linked to interpretations of bodily alterations, with the somatosensory cortex, including the postcentral gyrus, playing a key role in emotional processing. This study aimed to investigate the relationship between stress and microstructural white matter changes in the somatosensory cortex among healthy adults, crucial for early detection and treatment of stress in non-clinical populations. Materials and Methods: A total of 30 participants were recruited. The participants were administered the Depression, Anxiety, and Stress Scale 21 (DASS-21) questionnaire. All subjects underwent MRI brain scanning, with diffusion tensor imaging (DTI) used to assess white matter integrity. The association between stress scores in DASS-21 and DTI parameters was analyzed. Results: A significant negative correlation between stress scores and fractional anisotropy (FA) values in the left postcentral gyrus (r = -0.393, p = 0.32) was found, indicating early impairment by stress. No significant correlation was found in the right postcentral gyrus (r = -0.300, p = 0.107). Conclusion: Our research results demonstrated that the microstructural somatosensory cortex, especially the left postcentral gyrus, might have early changes impairment by stress using the technique of diffusion tensor imaging (DTI). Therefore, the microstructural white matter changes in the brain before suffering the disorder may be crucial and can be a novel potential biomarker for the early detection and intervention of the disease in the non-clinical population.